Night View, San Francisco and Bay - World's Fair on Treasure Island, Golden Gate International Exposition on San Francisco Bay (Stanley A. Plitz Company)
The Metropolitan area cities around San Francisco Bay will celebrate the completion of the world's largest Bridges in 1939 with a Fifty-Million Dollar International Exposition, to be built and held in center of San Francisco Bay. A most unique and picturesque site - The participation of foreign countries, especially those around "The Pacific" promises to make this the greatest "World's Fair" and finest Exposition of all time.